Design Enhancement of Methanol Purification in Syngas-Based Production: The Role of Additional Distillation and Cooling - Angela Gracelly; Jhilena Abigail Luberzky Sinuraya; Laurentia Auren Yoicy Talentina; Mathias Jesse Gandy; Rhadisza Octa Aslam Arnata; Siti Rodifatul Ilaiah (Journal of Chemical Engineering Research Progress, 2025)
Methanol is an essential industrial chemical with increasing global demand, yet conventional syngas-based production often encounters challenges related to energy efficiency and separation performance. This study seeks to design and evaluate an improved methanol purification process aimed at maximizing yield and purity through advanced heat management and separation strategies. Employing a rigorous process simulation environment and the Peng–Robinson Equation of State (PR-EOS) for thermodynamic modeling, a comparative analysis was conducted between a conventional base case and a modified process configuration. The base case comprised a single cooling unit, a separator, and one distillation column, whereas the modified design incorporated an additional upstream cooler and a secondary distillation column to enhance phase conditioning and recovery. Simulation results indicate that the proposed modifications substantially outperform the conventional design. The base case achieved a methanol purity of 59.26%, while the modified configuration increased purity to 71.07%. This 11.8% improvement demonstrates that multi-stage distillation combined with enhanced cooling effectively reduces vapor-phase losses and improves separation efficiency, offering a more sustainable pathway for industrial methanol production. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).